Pengarsipan Berbasis Dokumentasi Media Sosial “Gendis Sewu” dalam Perspektif Maqasid Syariah - Rachman, Rio Febriannur; Ghulam, Zainil (Idarotuna : Journal of Administrative Science, 2023)
This article discusses one of the public policies implemented by the Surabaya Library and Archives Service. This policy takes the form of documentation-based archiving on social media which is carried out in the Gendis Sewu program. The social media platforms used are websites, YouTube, and an application called "Taman Kalimas". Gendis Sewu is the Storytelling and Writing Movement Sewu, a training that is held every week in “Taman Bacaan Masyarakat” (Community Reading Parks) spread across 31 sub-districts throughout Surabaya. This storytelling and writing training has a target of "sewu", sewu in Javanese means a thousand. The program's target is thousands of children and teenagers whose literacy skills continue to be developed. The theories used are public policy, technological determination, maqasid Sharia, also reinforced by the concept of Sustainable Development Goals. The method used is qualitative with a literature study approach. This study explains how the implementation of this policy in society is seen from an Islamic perspective. The results of this research: 1) Archiving policies based on social media documentation are in accordance with principle stages such as planning, implementation and evaluation; 2) This kind of digital archiving is in harmony with a number of Sustainable Development Goals points where it occurs more effectively, efficiently and environmentally friendly; 3) This innovation has the spirit of Islamic teachings, seen from the concept of maqasid sharia al-ammah, which has an excellent service orientation for citizens.